2010
DOI: 10.1007/s11240-010-9868-4
|View full text |Cite
|
Sign up to set email alerts
|

A liquid culture system for shoot proliferation and analysis of pharmaceutically active constituents of Catharanthus roseus (L.) G. Don

Abstract: An efficient and cost effective micropropagation protocol using liquid medium was developed for Catharanthus roseus, a commercially important medicinal plant. Comparative analysis of shoot growth and proliferation in liquid Murashige and Skoog (MS) medium supplemented with different concentrations of cytokinins [6-Benzyladenine (BA), Kinetin (KN) and Thidiazuron (TDZ)] was conducted. Better response in terms of shoot proliferation, shoot diameter, number of leaves/shoot, number of branches/shoot, fresh weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
5
40
0
Order By: Relevance
“…On lesser volume of medium, the growth of cultures was slow and the medium dried up within a week; a volume of medium more than mentioned above caused hyperhydration of shoots, which affected shoot growth and multiplication. Reduction in the number and growth of shoots was due to hyperhydration which is a result of lower oxygen availability and submergence of shoots (Pati et al 2011). Time period of subculturing was found to be an important factor for the maintenance and multiplication of cultures.…”
Section: Shoot Multiplication In Liquid Mediummentioning
confidence: 99%
“…On lesser volume of medium, the growth of cultures was slow and the medium dried up within a week; a volume of medium more than mentioned above caused hyperhydration of shoots, which affected shoot growth and multiplication. Reduction in the number and growth of shoots was due to hyperhydration which is a result of lower oxygen availability and submergence of shoots (Pati et al 2011). Time period of subculturing was found to be an important factor for the maintenance and multiplication of cultures.…”
Section: Shoot Multiplication In Liquid Mediummentioning
confidence: 99%
“…Several authors have reported the value of liquid media for shoot multiplication (Russowski et al 2006;Pati et al 2011;Cavallaro et al 2014). However, S. alpina shoot tip explants placed in liquid culture, either agitated or stationary, did not derive shoots, and tissue necrosis was observed, probably caused by the continuous contact between the plant tissue and the liquid medium.…”
Section: Shoot Multiplicationmentioning
confidence: 99%
“…The elimination of agar from the culture medium also resulted in substantial savings in cost. Pati et al (2011) calculated a 5.2-fold reduction in cost associated with the use of liquid medium for Catharanthus roseus shoot multiplication.…”
Section: Quantification Of Flavones and Verbascoside In Multiple Shootsmentioning
confidence: 99%
“…Over recent decades, several attempts have been made to improve withanolide production by tissue culture (Ray and Jha 2001;Sharada et al 2007;Dewir et al 2010). Production of bioactive molecules by in-vitro liquid culturing techniques has gained considerable attention in recent years, and such methods are increasingly attractive alternatives to whole plant cultivation for production of high value phytochemicals (Pati et al 2010;Gawde and Paratkar 2012). …”
mentioning
confidence: 99%